Predictors of response to omalizumab and relapse in chronic spontaneous Urticaria: a narrative review focusing on parameters available in routine clinical practice - Mateu-Arrom, Laura; Vence Nogueira, Xenevra Adriana; Puig, Lluis; Spertino, Jorge (Frontiers in Allergy, 2025)
Chronic spontaneous urticaria (CSU) is a heterogeneous disease with variable responses to treatment. Identifying predictors of response to omalizumab and relapse after its discontinuation is essential for optimizing management. This narrative review aims to summarize current evidence, emphasizing clinically accessible parameters to provide a practical guide for physicians in routine care settings. Response to omalizumab appears to be influenced by the underlying pathophysiological subtype of CSU. Type IIB autoimmune CSU, associated with lower total IgE levels, higher IgG anti-thyroid peroxidase levels, basopenia, eosinopenia, elevated C-reactive protein, and greater disease activity, correlates with poorer responses. Coexisting inducible urticaria is associated with the need for longer duration of omalizumab therapy. Patients with higher body mass index may be poor responders to omalizumab at licensed doses but may benefit from dose escalation. Predictors of relapse after discontinuation include high baseline disease activity, which may be related to type IIB autoimmune CSU, and longer disease duration. Achieving complete disease control prior to tapering omalizumab may also reduce the risk of recurrence. In conclusion, clinically accessible parameters can assist in predicting response to omalizumab and relapse risk. These indicators can support individualized treatment decisions and counseling in daily practice. Further research is needed to refine relapse predictors and validate strategies such as treatment optimization.